Using adsorbent made from sewage sludge to enhance wastewater treatment and control fouling in a membrane bioreactor. Issue 20 (26th April 2016) - Pan, Zhihui; Zhang, Chaosheng; Huang, Bin
Abstract: An adsorbent prepared from rich carbonaceous sewage sludge was added to membrane bioreactors (MBRs). The efficiency of wastewater treatment and membrane fouling were compared for a standard MBR, a reactor with additional sludge-based adsorbent (SBA)-MBR, and powdered activated carbon (PAC)-MBR. The removal efficiencies for dissolved organic carbon (DOC) and UV254, the heavy metal contents of effluent, extracellular polymeric substances (EPS), soluble microbial products (SMP), the sludge particle size, and the trans-membrane pressure of the three reactors were monitored for more than 100 d. The wastewater treatment efficiency of SBA-MBR (UV254 : 58.5%; DOC: 88.8%) was similar to that of PAC-MBR (UV254 : 62.3%; DOC: 90.1%) and better than MBR (UV254 : 47.8%; DOC: 85.9%). Moreover, SBA-MBR showed least membrane fouling. The findings are explained as follows: In SBA-MBR, the contents of EPS and SMP, which led to membrane fouling, were relatively low; the sludge comprised dense flocs of relatively large size; higher Fe and Al contents in SBA preferentially absorbed the colloid substances and EPS, and limited the adhesion of contaminants to the membrane surface.